A retrospective analysis of women-s chances to become pregnant after completion of chemotherapy: a single center experience - ŞEKER, MESUT; USTAALIOGLU, B. B. Oven; BILICI, A.; KEFELI, U.; Seker, MESUT; SALEPCI, T.; UNAL, O.; GUMUS, M. (My University, 2011)
Purpose: With the improvement in anticancer therapies, the survival of women with malignancies has increased and infertility may affect the quality of life of premenopausal women, who experience temporary or permanent amenorrhea due to chemotherapy. The aim of this study was to review the rate of pregnancies among women with malignancy previously treated with chemotherapy.